RELAPSE OF GUILLAIN-BARRE SYNDROME AFTER SPINAL ANESTHESIA: A CASE REPORT - Memon, Nazima; N K, Nandanwankar; R G, Pathak (International Journal of Clinical and Biomedical Research, 2015)
Guillain-Barre Syndrome (GBS) is an acute inflammatory demyelinating polyneuropathy characterized by progressive symmetric ascending muscle weakness, paralysis and hyporeflexia with or without sensory or autonomic symptoms. It is most commonly caused by an autoimmune response of the body to an infectious agent like Campylobacter jejuni. It is less common during pregnancy but it may relapse during postpartum period. Cases of GBS have been reported after Spinal, epidural and general anesthesia. Here we report a case of 28year old female patient who had relapse of GBS after undergoing emergency laparotomy for ruptured ectopic pregnancy. In this case report, we are presenting an unusual case of GBS relapsing 4 years after initial episode following spinal anesthesia. KEYWORDS: Guillain-Barre Syndrome; Campylobacter jejuni; Postpartum period.